AL-QUR'ANIC INSTRUCTIONS ON STUD AL-QUR'ANIC INSTRUCTIONS ON STUDY AND LEARNING: AL-QUR'ANIC INSTRUCTIONS ON STUDY AND LEARNING (PENDAIS, 2024)
AbstractIn the process of thinking or reasoning is a form of human activity to gain knowledge and this can be said to be a form of learning and learning process. The process of Islamic education goes hand in hand with the efforts of the Holy Prophetsa in developing religion. Therefore, Islamic religious education is a basic need for every Muslim, and in principle the study of the concept of Islamic Education will lead to the concept of religious sharia because after all, religion must be the root of education. The methods of the Qur'an in learning and learning are: Method of dialogue or discussion, method of story, method of parable, method of example, method of practice or repetition, Method of 'Ibrah and Mau'izhah, Method of Targhib and TarhibKeywords: Learning, Learning, Method